Mathematical Modelling of Oscillatory Processes in Transmission of Movement of an Electric Drive with Non-Linear Long Elastic Elements - Andriy Chaban; Tomasz Perzyński (Communications - Scientific letters of the University of Zilina, 2021)
Mathematical model of transmission of movement of an electric drive system that includes long elastic elements, including the non-linear relation between tensors of strength and deformation is presented in this article. Mentioned type of transmission is applied in the tasks related to special-purpose transport. A method that is based on integral modification of variational Hamilton-Ostrogradsky principle was applied for the presented model. Results of the computer simulation of oscillatory processes in transmission of movement of an electromechanical system are presented in the article.